Agostinho da Silva – da Ciência à Escola do Conhecimento - Briosa e Mota, Helena (História da Ciência e Ensino: construindo interfaces, 2019)
Resumo Segu(i)ndo as pistas e rota desenhada por Agostinho, reflectiremos sobre modelos de escola; adicionalmente, serão apresentados alguns dos cadernos de divulgação cultural escritos para A Mocidade e A Juventude dedicados à Ciência. A terminar, sugerem-se propostas de leitura e tratamento pedagógico interactivo e interdisciplinar para os vários graus de ensino. Palavras-chave: Agostinho da Silva – Cadernos «À Volta do Mundo» para a Mocidade e Juventude – organização de escola – interacção – interdisciplinaridade Abstract To show life, its eternal creative effort, the continuous progress of science, the beauty of the mathematical expression, the essential contribution of the scientific activity to the improvement of the organization of the whole world, that’s the mission of a real school.»1 Following the clues given by Agostinho da Silva where «Real Schools» in fact appear as models of non-virtual educational success, we’ll discuss models of school organizations different from the current ones. Additionally, we’ll present some of the Da Silva’s contributions to the dissemination of scientific knowledge by means of informative publications for teenagers, along with concrete proposals of interactive approach for primary and secondary education. Keywords: Agostinho da Silva – Cadernos «À Volta do Mundo» para a Mocidade e Juventude – school organization – interaction – interdisciplinarity